2016
DOI: 10.1016/j.biocel.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin-like modifier FAT10 in cancer development

Abstract: a b s t r a c tDuring the last years it has emerged that the ubiquitin-like modifier FAT10 is directly involved in cancer development. FAT10 expression is highly up-regulated by pro-inflammatory cytokines IFN-␥ and TNF-␣ in all cell types and tissues and it was also found to be up-regulated in many cancer types such as glioma, colorectal, liver or gastric cancer. While pro-inflammatory cytokines within the tumor microenvironment probably contribute to FAT10 overexpression, an increasing body of evidence argues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 103 publications
2
66
0
Order By: Relevance
“…Under the catalytic action of E1 and E2 enzymes, FAT10 binds to substrates by FAT10ylation to form FAT10–substrate complexes, which enter the proteasome for degradation . Recently, there is accumulating evidence that FAT10 is up‐regulated in a variety of malignancies, including HCC, and that FAT10 overexpression is related to the prognosis of tumor . Our and other studies demonstrated that the increase of FAT10 expression could promote HCC cell proliferation .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Under the catalytic action of E1 and E2 enzymes, FAT10 binds to substrates by FAT10ylation to form FAT10–substrate complexes, which enter the proteasome for degradation . Recently, there is accumulating evidence that FAT10 is up‐regulated in a variety of malignancies, including HCC, and that FAT10 overexpression is related to the prognosis of tumor . Our and other studies demonstrated that the increase of FAT10 expression could promote HCC cell proliferation .…”
Section: Discussionsupporting
confidence: 55%
“…Recently, multiple studies have found that abnormal FAT10 expression is closely related to the occurrence and development of tumors. FAT10 is highly expressed in various tumors, including hepatocellular carcinoma (HCC), and closely related to tumor proliferation, invasion and metastasis, and prognosis . Therefore, FAT10 is considered an oncogene.…”
mentioning
confidence: 99%
“…Top genes upregulated at least 2-fold in MLL- vs. AT1-TINT were for example, Scl30a2 –an epithelial Zn-transporter shown to be central for prostate function [45], Grhl3 –a factor that promotes cell migration and invasion [46], Ubd –a factor that promotes tumor growth and regulates immune responses [47], Il12rb2 –an immune regulatory factor [48], Plau –a stroma remodeling factor that promotes invasion and metastasis [49], Clu —an immune response- and apoptosis regulating factor [50], Efna5 –a factor suggested to be involved in prostate cancer [51], Parm1 –an androgen-regulated factor that influence apoptosis in prostate epithelial cells [52], Edn1 –a factor that promotes prostate cancer growth [53], Serpine1 –a factor regulating Plau (see above, [49]), Vtcn1 –a factor that restricts antitumor T-cell responses and is associated with metastasis [54], Mmp15 and Mmp7 –factors that promote stroma remodeling [55], Sulf1 –a factor involved in prostate development and cancer [56], S100a11 –a factor that promotes prostate cancer progression [57], Ctgf –a stroma stimulating factor [58], and Cyr61 –an angiogenic factor that is associated with prostate cancer progression [59]. …”
Section: Resultsmentioning
confidence: 99%
“…And FAT10 was reported being up-regulated in several tumor types including tumors of the liver and colon [Lee et al, 2003][Lukasiak et al, 2008][Qing et al, 2011][Yan et al, 2010]. Although the mechanism of FAT10 promalignant function remains unclear, many researchers have re-ported that the expression of FAT10 increased with Akt, NF-κB/STAT3 [Gao et al, 2013][ Liu et al, 2014], CXCR4/7[Gao et al, 2013], MAD2 [Theng et al, 2014], p53 [Choi et al, 2014], and β-catenin/TCF4 [Aichem et al, 2016], in addition to its signal for proteasomal degradation [Schmidtke et al, 2014]. Previously, we reported that FAT10 plays an essential role in MDB formation and tumorigenesis [Oliva et al, 2008, 2010][French et al, 2012].…”
Section: Discussionmentioning
confidence: 99%